Non-fungible token: a promising digital tool for business - N. A. Kashevarova; I. S. Starikova (Вестник университета)
This paper presents a review of the current status and development trends of the non-fungible tokens’ technology (NFT), which are digital rights to unique objects recorded in the blockchain. The object of the study is the non-interchangeable token technology. The subject of the study is the fields of practical application of NFT. The method is an analytical review of scientific publications. The current state and socio-cultural sources of the NFT market related to works of art and media objects are analysed. The technological and legal problems preventing the wide spread of NFT in the business environment are identified. The prospects for the use of non-fungible tokens in the field of protection and commercialization of patent law objects are considered.